The Effect Of Service Quality And Trust On Consumer Satisfaction Users Of Online Grab Ojek Transportation In Bima City - waliyul andri; kartin aprianti (Jurnal Ilmu Manajemen Profitability, 2022)
This study aims to determine the effect of service quality and trust partially and simultaneously on consumer satisfaction using online ojek transportation user sGrab in Bima City. The approach used in this research is using an associative approach. The population in this study is all consumers who use Grab in the city of Bima with a sample of 96 respondents with the sampling technique used is purposive sampling. Data collection techniques used are observation, questionnaires, and literature study. The data analysis technique used was validity test and reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination and t test and F test processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results showed that service quality and trust partially and simultaneously have a positive and significant effect on consumer satisfaction using online ojek transportation users Grab  in Bima City